The welfare cost of excess volatility in incomplete markets with sunspots - Kang, Minwook (2021)
In an incomplete markets economy with sunspots, the Pareto-criterion cannot rank sunspot equilibria of different levels of excess price-level volatility. Therefore, I propose a measure of excess volatility cost in terms of a period-0 endowment good. Ex-ante endowment subsidies are provided, in theory, to each consumer, so that the resulting equilibrium allocation of the higher volatility is Pareto-equivalent to the original benchmark equilibrium with a lower volatility level. The aggregate volatility cost is computed as the sum of all consumers' subsidies. Focusing on local analysis that considers small variations around a given volatility level, I show that the aggregate cost strictly increases in volatility even though each individual cost does not necessarily have this property.